Asesmen Daya Saing Ekonomi Daerah dengan Pendekatan Model Dynamic - Muhrisya, Ashabul Kahfi; Sabar, Wardihan (ICOR: Journal of Regional Economics, 2021)
Economic conditions and potential in each region are the basic capital and the main factor in the regional economic development strategy. The purpose of this study is to study the potential for growth in each of the economic sectors in Wajo Regency, as well as look at the level of competitiveness in each of these sectors in order to increase which sector-based sectors have strong competitiveness as a source of regional economic strength. This research uses descriptive quantitative by using secondary data in the form of time series (time series) from the GRDP of South Sulawesi Province and Wajo Regency for the period 2013-2017. The analysis techniques used are Location Quotient (LQ), Dynamic Location Quotient (DLQ), Distribution Ratio Model (MRP), and Overlay analysis. The results of this study indicate three sectors that are recommended as sector bases in the future. The results of this study also show the fact that there are two sectors that have better competitiveness as well as comparative which are superior compared to the same activities at the Provincial level namely the Electricity and Gas Sector; and the Trade Sector Keywords: Dynamic Model Approach, Economic Competitiveness, Overlay Analysis.